Gambling – causes, diagnosis, criteria, spreading - Pyłypczuk, Aneta; Makara-Studzińska, Marta; Urbańska, Anna (Current Problems of Psychiatry, 2011)
The aim of the thesis was an explanation of the term “pathological gambling”, description of its history, causes and spreading in Poland and worldwide as well as presentation and comparison of criteria concerning the diagnosis of pathological gambling in various international classifications of mental disorders i.e. DSM-III, DSM-IV and ICD-10. Method: With the use of Medline and EBSCO databases, we screened for different pieces of medical literature that contained the following keywords: gambling, addictions and criteria. The literature was published in years 2005-2010 in English as well as in Polish language and was entirely devoted to the subject of gambling and the classification of psychiatric illnesses. From the theses that included the keywords, we chose those that concerned the analysis of diagnostic criteria regarding the diagnosis of pathological gambling in the international classifications of mental illnesses. On the grounds that there are only a few theses dedicated to this kind of subject, we widened the time range for the researched publications (from 2000 to 2010). The results have shown that the history of gambling is far-reaching and that currently pathological gambling is an increasingly serious problem not only in Poland, but also worldwide. The causes of gambling addictions are inconclusive, however, on the basis of the research we can presume that there is a number of factors that influence people to be predisposed to this particular disorder.